Secondary metabolites in elaeocarpus grandiflorus cell culture in WPM medium with various concentrations of PGR. (April 2020) - Anggraito, Y U; Nugrahaningsih, W H; Musafa, F; Mukhtar, K; Wijawati,; Rostriana, Y; Safitri,; Habibah, N A
Abstract: This study aims to analyze the influence of plant growth regulator (PGR) for secondary metabolites production in Elaeocarpus grandiflorus cell culture. Picloram (3.5, 5 and 7.5 ppm) and 2, 4-D (1.5, 2.5 and 3.5 ppm) were used as PGR of cell suspension culture. Cell cultures were obtained from callus grown in liquid WPM medium with various concentrations of PGR. Culture is maintained in shakers at a speed of 120 rpm in dark conditions. Harvesting is done after the age of culture reaches 30 days. Extraction was done by the maceration method with methanol as a solvent. A qualitative test using a thin layer chromatography test (TLC) was conducted to analyze the presence of various secondary metabolites. Phenolic quantitative tests were performed using a spectrophotometer using gallic acid standard compounds. The results showed that the cell culture contained alkaloids, phenolics, terpenoids, flavonoids. All treatments showed the presence of phenolic with varying total phenolic concentrations. PGR affects the type and concentration of secondary metabolites produced by E. grandiflorus cell suspension culture.